THE EFFECT OF USING THE STRATEGIES OF BRAINSTORMING AND COMPUTER EDUCATION IN ACADEMIC ACHIEVEMENT AND THE DEVELOPMENT OF CREATIVE THINKING SKILLS OF SIXTH GRADE STUDENTS IN JORDAN AND THEIR ATTITUDES TOWARDS LEARNING MATHEMATICS - Sdouh, Walid Mahmoud (European Scientific Journal, ESJ, 2013)
This study aimed to investigate the effect of using the strategies of brainstorming and computer education in academic achievement and the development of creative thinking skills among the students of sixth grade and their attitudes towards learning the engineering unit in Mathematics, The study sample consisted of students from Berketen school for the academic year 2012-2013, spread over two experimental groups. The first included 34 students who used the brainstorming strategy. The second group included 35 students and used the strategy of computer education. The study showed that there are differences with statistical significance in (∝ ≥,05) among the averages of the academic achievement as well as the skills of creative thinking of the two groups. The results went for the benefit of the experimental group that used the strategy of brainstorming. Moreover, the study showed that there are differences with statistical significance in (∝ ≥,05) for the group that used the strategy of computer education to learn the engineering unit.